Modeling natural photic entrainment in a subterranean rodent (Ctenomys aff. knighti), the tuco-tuco - Flôres, Danilo E. F. L. (2013)
Subterranean rodents spend most of the day inside underground tunnels, where there is little daily change in environmental variables. Our observations of tuco-tucos (Ctenomys aff. knighti) in a field enclosure indicated that these animals perceive the aboveground light-dark cycle by several bouts of light-exposure at irregular times during the light hours of the day. To assess whether such light-dark pattern acts as an entraining agent of the circadian clock, we first constructed in laboratory the Phase Response Curve for 1 h light-pulses (1000lux). Its shape is qualitatively similar to other curves reported in the literature and to our knowledge it is the first Phase Response Curve of a subterranean rodent. Computer simulations were performed with a non-linear limit-cycle oscillator subjected to a simple model of the light regimen experienced by tuco-tucos. Results showed that synchronization is achieved even by a simple regimen of a single daily light pulse scattered uniformly along the light hours of the day. Natural entrainment studies benefit from integrated laboratory, field and computational approaches.